Sugarcane straw as a potential second generation feedstock for biorefinery and white biotechnology applications. (January 2021) - Aguiar, André; Milessi, Thais Suzane; Mulinari, Daniella Regina; Lopes, Melina Savioli; da Costa, Sirlene Maria; Candido, Rafael Garcia
Abstract: Sugarcane straw (SCS) represents about one-third of the total primary sugarcane energy. Since its burning in pre-harvesting periods has been banned in Brazil, SCS available amount has grown, and the development of valuable applications for this lignocellulosic material became crucial for the development of a circular economy. An attractive and current alternative is its application in combustion processes for energy generation. However, in the biorefinery concept, the SCS processing as a potential feedstock for the obtainment of bioproducts and biomaterials, such as ethanol, xylitol, biogas, enzymes and oligosaccharides, has also attracted a great deal of attention. Thereby, this work provides a comprehensive review of the progress of SCS processing aimed at its valorization through the production of high-value products and the development of environmental-friendly and cost-effective processes. Graphical abstract: Image 1 Highlights: Sugarcane straw presents interesting composition for sustainable processes. Sugarcane straw availability has increased in Brazil due to changes in sugarcane harvesting. Its composition varies according to material-collection location, weather conditions, plant development period, and variety. It can be used as feedstock to produce bioenergy, biofuels, composites, and as adsorbent. Exploration of sugarcane straw as feedstock in biorefineries is still few reported.